MODEL PELAKSANAAN BIMBINGAN KONSELING BERBASIS TEKNOLOGI INFORMASI DAN KOMPUTER BAGI SISWA BERKEBUTUHAN KHUSUS - Husni Abdillah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Students with special needs have unique characteristics that distinguish them from other students in general. These unique characteristics sometimes cause various obstacles in the learning process. Counseling guidance as part of the education system aims to support the learning process of students with special needs so that they can be more optimal in learning. In its implementation, counseling guidance for students with special needs experiences several obstacles that may be overcome through the application of information and communication technology in the process. This study aims to formulate a model for implementing information and communication technology-based counseling guidance for students with special needs. The research method used is a systematic review of six journals obtained from searching using Google Scholar with three keywords, namely counselling, disability, and information technology. The results showed a variety of supporting and inhibiting factors, needs and targets, as well as the stages of implementing information and communication technology-based counseling guidance for students with special needs. The results are expected to broaden insights into innovative counseling guidance models that can meet the diverse needs of students with special needs.